224k views
0 votes
4x^2+64=0 solve by any method

1 Answer

4 votes

For this case we have the following quadratic equation:


4x ^ 2 + 64 = 0

The solutions are given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Where:


a = 4\\b = 0\\c = 64

Substituting we have:


x = \frac {-0 \pm \sqrt {(0) ^ 2-4 (4) (64)}} {2 (4)}\\x = \frac {\pm \sqrt {0-1024}} {8}\\x = \frac {\pm \sqrt {-1024}} {8}

We have to by definition:


i ^ 2 = -1\\x = \frac {\pm \sqrt {1024i ^ 2}} {8}\\x = \frac {\pm i \sqrt {1024}} {8}\\x = \frac {\pm32i} {8}

We have two roots:


x_ {1} = + \frac {32i} {8} = 4i\\x_ {2} = - \frac {32i} {8} = - 4i

Answer:

We have two complex roots:


x_ {1} - = + 4i\\x_ {2} = - 4i

User Carroll
by
5.7k points